Inculcating ethical values in the students through e-Learning platform - M., Abdul Hafeez; A., Farooq; Shah, Asadullah; M, Rosydi (2013)
with the encompassing speed of Information and Communication Technologies (ICTs), the world is developing with time; the gap between the have and have not is widening. The greed for materialistic and worldly things is increasing. The trend can be partially contributed to the modern education system, where total emphasis is on domain and technical knowledge. Teaching of moral values is considered as an integral part of the education in Islam. The contents of our formal education syllabi are gradually throwing out material on character development. With the busy schedule of individuals, the role of character development by the family and society is diminishing. The only hope is left with the teacher. In the e-Learning platefrom that hope is also disappearing because of physical absence of teacher. The work will analyze the learning models and role of ethical development. It is also proposing a model using ICTs which can help in the character de